Use of rescue high frequency oscillation ventilation in neonates with acute respiratory failure after failing conventional ventilation - Kumble, Ali; Phadke, Abhishek K.; Shafi, Shakib (International Journal of Research in Medical Sciences, 2021)
Background: High frequency oscillatory ventilation (HFOV) is a newer mode of ventilation in neonates. The objective of this study was to study the efficacy of rescue HFOV in improving the oxygenation and ventilation in neonates with acute respiratory failure after failing synchronised intermittent mandatory ventilation (SIMV). Methods: A prospective observational study was conducted over a period of 12 months. Neonates with respiratory distress requiring ventilation on SIMV mode based upon the unit protocol were included in the study. Babies who have failed on SIMV were then switched over to HFOV. The primary outcome measures were oxygenation index (OI), ventilation: alveolar-arterial oxygen gradient (AaDO2) and duration of ventilation with a secondary outcome measure of mortality and complications associated with ventilation. Results: A total of 65 babies were ventilated out of which 11 babies required high frequency oscillatory ventilation as per the study protocol. Of 11 neonates who were oscillated eight (72.7%) improved and survived. Among the babies who survived OI<13 was seen in a total of six babies in the first three hours of oscillation and OI<10 was seen in two babies. There was no statistically significance difference in the incidence of intra-ventricular haemorrhage (IVH) and pneumothorax between HFOV and SIMV group. Conclusions: High frequency oscillatory ventilation was found to improve short term oxygenation and ventilation in neonates who failed SIMV. HFOV is not associated with increased risk of pneumothorax or IVH.